Analysis the Work-Life Balance Among Female Lecturers in Colleges of Thane District: A Study of Work-Life Balance and Career Advancement among Female Lecturers in Thane District (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Work life balance gives the bonds that hold a person with their work and personal life. To be balanced with work and life, individual should know himself or herself. Here a portion of the scientists express their examination report about work life balance. The work environment therefore plays a vital role in maintaining a balance in the lives of female lecturers. Flexible job arrangements may accommodate the demands of their communities. The present research is therefore an effort to address the issue of woman lecturers, their degree of target fulfillment and the variables that affect career advancement.